PERANCANGAN APLIKASI MOBILE LEARNING TEST OF ENGLISH FOR INTERNATIONAL COMMUNICATION (TOEIC) SIMULATION PADA SMARTPHONE BERBASIS ANDROID - Yayang Fitria Chandra; Nurindah Dwiyani; Yasdinul Huda (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2017)
English is the language most widely used in the world. English is the most popular in the world while the language most widely adopted as the official language in several countries and international organizations. There are 53 countries and 10 international organizations that use English as the official language. In addition, almost all countries in the world would adopt English as a second language after their own national language. In the working world, some companies generally use TOEIC to help find qualified employees to speak English. TOEIC is a test used to measure a person's ability to speak English. In TOEIC, there is a series of tests to be done. TOEIC score itself is widely used for the requirements for the company. For example, PT Pertamina (Persero).The course fee and cost Toeic tests are relatively expensive to make the most of those who need to learn self-taught TOEIC score and perform simulation before following Toeic test. But the self-taught through books deemed less effective, uninteresting, monotonous, boring and can not be used in dark places. And applications for free circulation in the Play Store app is paid mostly.Applications will Toeic authors designed using the Java programming language and Eclipse as editor, and is a free application that can be used offline. The TOEIC app provides four main menu tips and tricks, Toeic simulation, solution, and about. On the menu Tips and Tricks provides ways TOEIC do the problems easily. On the menu Toeic simulation contains questions TOEIC. On the menu solution contains a discussion of the TOEIC simulation has been done so that the user can understand TOEIC matter of discussion given. About the last menu contains applications and resources TOEIC questions. Keywords: Application, Mobile Learning, Toeic, Android, Smartphone.